2023
DOI: 10.1007/s13304-023-01613-5
|View full text |Cite
|
Sign up to set email alerts
|

How future surgery will benefit from SARS-COV-2-related measures: a SPIGC survey conveying the perspective of Italian surgeons

Abstract: COVID-19 negatively affected surgical activity, but the potential benefits resulting from adopted measures remain unclear. The aim of this study was to evaluate the change in surgical activity and potential benefit from COVID-19 measures in perspective of Italian surgeons on behalf of SPIGC. A nationwide online survey on surgical practice before, during, and after COVID-19 pandemic was conducted in March–April 2022 (NCT:05323851). Effects of COVID-19 hospital-related measures on surgical patients’ management a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Further studies have shown a growing use of telemedicine during the COVID-19 pandemic in western countries using telematic consultations, too, promising a permanent role in future telematic postoperative follow-up [ 21 ]. Although studies have shown the positive benefit of telemedical consultations in general, to date, only few studies have examined POCUS in rural [ 22 ] or urban emergency settings [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have shown a growing use of telemedicine during the COVID-19 pandemic in western countries using telematic consultations, too, promising a permanent role in future telematic postoperative follow-up [ 21 ]. Although studies have shown the positive benefit of telemedical consultations in general, to date, only few studies have examined POCUS in rural [ 22 ] or urban emergency settings [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing use of virtual reality research, virtual meetings, online education initiatives, and telehealth, initially introduced out of necessity during the COVID-19 pandemic, represent interesting tools to expand their knowledge and research among low-income country residents. [ 1 , 17 , 21 , 24 , 31 , 40 ] By networking and exchanging knowledge with experts in the field, low-income hospitals can enhance their microsurgical training opportunities and stay updated with the latest advancements.…”
Section: Discussionmentioning
confidence: 99%